Sistem Pembatasan Jaringan Internet Wi-Fi berbasis Voucher menggunakan Perangkat MikroTik - Akmal Tamar Jaya; Suroso Suroso; Irawan Hadi (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
The high mobility in this information technology era has led many people to use wireless (Wi-Fi) internet access media instead of wired media. Devices such as laptops, tablets, PCs, and gadgets are inseparable from wireless technology. This study aims to limit Wi-Fi users and improve the efficiency and performance of the hotspot network. This study implements a voucher system using MikroTik devices and AAA (Authentication, Authorization, and Accounting) functions. The research development method uses a waterfall model consisting of 5 stages: requirements analysis, topology design, system implementation, performance testing, and maintenance. Data collection techniques involve direct observation of hotspot users who use vouchers, recording data on voucher duration, the number of users, and usage time. The collected data is analyzed quantitatively to evaluate the efficiency and performance of the voucher system and to gain insights into user experiences. The research results show successful implementation with 1, 3, 5, 8, 15, and 20 users using vouchers for 30-, 60-, and 120 minutes during morning, afternoon, and evening testing periods. Based on the testing and data analysis, this voucher-based Wi-Fi user restriction system successfully improves the efficiency of the Wi-Fi hotspot network by reducing the risk of illegal access and data theft.